CONCEPTUAL BASES OF IMPROVEMENT OF THE STATE REGULATION OF PASSENGER TRANSPORT OF THE MEGALOPOLIS - Petrenko, Oleksandr (Theory and Practice of Public Administration, 2019)
The article summarizes the conceptual basis for improving the state regulation of passenger transport in the metropolis. It is proved that the basis of regulation of passenger transport processes, especially on public transport, which is financed from the city budget, is information about the planned and actual indicators of transport work of carriers, and the correctness of management decisions depends on the reliability of primary information. Accordingly, to improve the efficiency of transport complex management at the level of the metropolis, it is necessary to ensure the reliability of primary information on the performance of transport work, as well as the availability of primary data of all structures that ensure the transport process. There is a need to create an effectively functioning urban information system in the field of transport. It is determined that the functions of regulating passenger traffic in the metropolis, should be assigned to the organization (state institution), which will be administratively independent of the carriers. This institution should concentrate all the primary information about the work of transport of the metropolis, collected with the help of technical means, the reliability of which will be independent of the human factor. It was found that the state institution of passenger traffic management of the metropolis is advisable to assign the following main functions: the formation of indicators of planned work and schedules of rolling stock on the route network of the metropolis; fixing the actual work of the rolling stock and operational dispatching traffic control on the entire route network of the metropolis; preparation of reports on the work of the rolling stock on the line to cover the costs of carriers from the budget (for work on social routes).